quiz8solutions - MAC1147: Quiz #8 10/27/2009 In the...

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: MAC1147: Quiz #8 10/27/2009 In the top-right corner of a clean sheet of paper, write your name, UFID, and section number. Please use a pen with blue or black ink. When you are nished, FOLD your paper in half lengthwise and write your name on the back. 1. Consider the equation: 2 ln(x) + ln(x + 3) = ln(4x) (a) State the one-to-one property for logarithmic functions: If loga x = loga y , then x = y (b) Finish the statement of the following property: n · loga u =loga (un ) (c) Finish the statement of the following property: loga u + loga v = loga (uv ) (d) Use parts (a), (b), and (c) to solve the equation above. 2 ln(x) + ln(x + 3) = ln(4x) ⇒ ln(x2 (x + 3)) = ln(4x) ⇒ x3 + 3x2 + 4x = 0 ⇒ x(x + 3)(x + 1) = 0 ⇒ x = 0; x = −3; x = −1. But x = −3 is not in the domain, so only x = 0 and x = −1 are solutions. 2. Let f (x) = ln(3x − 4), and let g (x) = e2x + 1 (a) Find the domain of (f ◦ g )(x) (f ◦ g )(x) = f (g (x)) = f (e2x +1) = ln(3(e2x +1) − 4) = ln(3e2x − 1). The domain of ln(x) is (0, ∞), so we must set 3e2x − 1 > 0 ⇒ e2x > ln( 1 ) ln( 1 ) 1 ⇒ x > 23 , or ( 23 , ∞) in interval notation. 3 (b) Find g −1 (x) x = e2y + 1 ⇒ e2y = x − 1 ⇒ ln(x − 1) = 2y ⇒ g −1 (x) = 1 ln(x−1) 2 ...
View Full Document

This note was uploaded on 12/27/2011 for the course MAC 1147 taught by Professor German during the Summer '08 term at University of Florida.

Ask a homework question - tutors are online